Effect of two tapering methods on interleukin-6, cortisol and performance in elite male wrestler - Mehranpour, A.; Supaporn, S.; Hasani, S.Mitranun, W.; Jourkesh, M. (Sport Science - International Scientific Journal of Kinesiology, 2015)
The purpose of this study was to compare the effect of two types of tapering on interleukin-6(IL-6), cortisol and performance in elite male wrestler. After 4 weeks of progressive training, wrestler was randomly divided into three equal groups, 1-control group (N=10) continued performing progressive training for one week, 2- taper group 1 (N=10) continued with a 50% reduction in training volume for one week, 3-taper group 2 (N=10) continued with a 75% reduction in volume of training for one week. Plasma blood IL-6 and cortisol levels were assayed from analysis obtained via standard ELISA. Also general strength muscle was recorded as a performance test. All data were collected before and after progressive training and also after one week tapering period. Result: There were significant reduction IL-6 and cortisol levels among both tapering group with control group (P.0.05). There was significant reduction of IL-6 and cortisol levels among tapering 50% and tapering 75% after tapering period (P.0.05). Also there was significant increase in general strength muscle between tapering 75% and control group (P.0.05). Hence, one week tapering with 75% reduction in training volume after progressive training while the intensity kept high is effective strategy for reduction IL- 6, and cortisol levels and also increase performance. It seems that higher reduction of training volume when the intensity kept high is a good strategy for wrestler before main competition.